A simple and efficient method to identify replacements of P-lacZ by P-Gal4 lines allows obtaining Gal4 insertions in the bithorax complex of Drosophila. - de Navas, L.; Foronda, D.; Suzanne, M.; Sanchez-Herrero, E. (Mechanisms of Development, 2006)
The functional replacement of one gene product by another one is a powerful method to study specificity in development and evolution. In Drosophila, the Gal4/UAS method has been used to analyze in vivo such functional substitutions. To this aim, Gal4 lines that inactivate a gene and reproduce its expression pattern are required, and they can be frequently obtained by replacing pre-existing P-lacZ lines with such characteristics. We have devised a new method to quickly identify replacements of P-lacZ lines by P-Gal4 lines, and applied it successfully to obtain Gal4 insertions in the Ultrabithorax and Abdominal-B Hox genes. We have used these lines to study the functional replacement of a Hox gene by another one. Our experiments confirm that the abdominal-A gene can replace Ultrabithorax in haltere development but that it cannot substitute for Abdominal-B in the formation of the genitalia.